2002
DOI: 10.1111/j.1527-3458.2002.tb00232.x
|View full text |Cite
|
Sign up to set email alerts
|

YM872: A Selective, Potent and Highly Water‐Soluble α‐Amino‐3‐Hydroxy‐5‐Methylisoxazole‐4‐Propionic Acid Receptor Antagonist

Abstract: This review focuses on the in vitro and in vivo neuropharmacology of YM872, a potential neuroprotective agent currently undergoing clinical trials in the United States (trial name: AMPA Receptor Antagonist Treatment in Ischemic Stroke -ARTIST). Its neuroprotective properties in rats and cats with induced focal cerebral ischemia are described. YM872, [2,3-dioxo-7-(1H-imidazol-1-yl)-6-nitro-1,2,3,4-tetrahydroquinoxalin-1-yl]-acetic acid monohydrate, is a selective, potent and highly water-soluble competitive á-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 48 publications
0
30
0
Order By: Relevance
“…73 Moreover, recent reports have suggested both the competitive AMPAR antagonist YM872 (12, Fig. 4), 74 as well as the noncompetitive antagonist GYKI 53784 (14, Fig. 5), 75 as potential drugs.…”
Section: Ampar Antagonistsmentioning
confidence: 98%
“…73 Moreover, recent reports have suggested both the competitive AMPAR antagonist YM872 (12, Fig. 4), 74 as well as the noncompetitive antagonist GYKI 53784 (14, Fig. 5), 75 as potential drugs.…”
Section: Ampar Antagonistsmentioning
confidence: 98%
“…It is of interest that, while AMPA antagonists showed neuroprotective efficacy in certain preclinical settings of both focal and global cerebral ischemia Gill, 1994;Xue et al, 1994;Lees, 2000;Takahashi et al, 2002), the successful completion of larger clinical trials has not been reported. In a phase II double-blind multicenter trial (Elting et al, 2002), the AMPA antagonist ZK200755, when administered in a higher dose, produced a marked transient worsening of the NIHSS score attributable to a depression of consciousness (stupor or coma).…”
Section: Ampa Receptor Antagonismmentioning
confidence: 99%
“…These include calcium channel blockade [23], calcium chelation [24], free-radical trapping [25], gamma-aminobutyric acid (GABA) and serotonin agonism [26, 27], and alpha-amino-5-hydroxy-3-methyl-4-isoxazole propionic acid (AMPA) and N-methyl- d -aspartate (NMDA) receptor antagonism [28, 29]. While a large number of neuroprotective agents have been shown to successfully reduce infarct size in animal models of focal and global ischaemia, neuroprotective compounds administered as monotherapy have failed to demonstrate efficacy for the treatment of AIS in phase III clinical trials in humans [15, 30, 31].…”
Section: Neuroprotection: Aims and Approachesmentioning
confidence: 99%